UMP Chairman: Tall order, but achievable - Mohd R, Jamaludin
“It may be a tall order, but definitely achievable,” remarked Dato’ Mohd Hilmey Mohd Taib, the Chairman of the Board of Directors (BoD) of Universiti Malaysia Pahang (UMP), in a recent exclusive personal interview with the Publication & Graphics Unit of the university’s Vice-Chancellor’s Office.